Serum Copper, Iron, and Total Iron Binding Capacity in Hypothyroidism: A Case Control Study - Manger, Priyanka Thapa; Yadav, Gyanendra Kumar; Tiwari, Dhananjay; Awasthi, Richa; Verma, Durga Prasad (Cell and BioPharmaceutical Institute, 2023)
Background: Thyroid hormone metabolism is linked to iron metabolism. Thyroperoxidase, a key enzyme in the biosynthesis of thyroid hormones, is iron-dependent. Thus, iron deficiency might be the primary cause of hypothyroidism. Copper is another trace element that has been linked to thyroid status. Copper regulates excessive thyroxine (T4) absorption and reduces cell damage during thyroid hormone synthesis. The present study clarified the possible correlations between iron and copper levels as well as total iron binding capacity (TIBC) and triiodothyronine (T3), T4, as well as thyroid-stimulating hormone (TSH) levels in healthy and hypothyroid subjects.Materials and methods: Thirty-five healthy subjects and 35 hypothyroid subjects were included in this study. Serum T3, T4, and TSH levels were measured using the enzyme linked fluorescence assay. Serum iron levels and TIBC were estimated using ferrozine/magnesium carbonate method, while serum copper levels were estimated using colorimetric method.Results: Copper levels were not significantly different between healthy and hypothyroid subjects. Iron and T4 levels were significantly lower in hypothyroid subjects compared with those in healthy subjects, while TIBC and TSH levels were significantly higher. There was no significant correlation between copper levels and T3, T4, and TSH levels.Conclusion: There were inverse correlations between TIBC and T4 as well as iron levels, and there was no significant correlation between copper levels and all thyroid function parameters. Routine examination of iron levels and thyroid function is highly recommended for early diagnosis and therapy of hypothyroidism.Keywords: total iron binding capacity, iron, copper, hypothyroidism